Efforts of Acts and Morals Teachers in Overcoming the Impact of Bad Character and Social Attitude on the ‘Durian Generation’ (Case Study of MIN 1 Yogyakarta) - Lativa, Lativa; Sibawaihi, Sibawaihi; Sulistiyowati, Endang (ALSYS, 2025)
The ‘durian generation,' like the current generation, has a critical, independent, and adaptive character to technological developments but is at risk of lacking spiritual depth and moderate moral values. Religious education, especially through Akidah Akhlak learning, is very important to form a balanced character based on Islamic values. This research aims to analyze the character of the durian generation and explore the role of Akidah Akhlak teachers in forming the character of students at MIN 1 Yogyakarta so that they can create a generation that is not only intelligent and critical but also has noble and moderate morals. The researchers used a qualitative research method through a literature review and observation of the practice of learning Akidah Akhlak in this school. Data were analyzed thematically to identify the characteristics of the durian generation and the role of teachers in character formation. The research results showed that Akidah Akhlak teachers play a strategic role as character-forming agents by implementing contextual learning methods and innovative media according to the character of the durian generation. Effective character formation includes the integration of the values ​​of moderation, tolerance, and noble morals so that students can develop into individuals who are balanced between intellectual, spiritual, and social. The challenges and opportunities that exist can be overcome with the creativity and commitment of teachers in adjusting learning methods to the dynamics of the times.